Hybrid Organizational Responses to Institutional Complexity: A Cross-Case Study of Three European Universities - Boitier, Marie; Riviere, Anne; Wenzlaff, Ferdinand; Hattke, Fabian (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
European universities traditionally embedded in the institutional logics of academic professionalism as well as democratization and regulation face the emergence of a new managerial logic generating conflicting demands and triggering hybrid organizational responses. This article investigates hybridization processes by analyzing how multiple institutional logics play out among organizational attributes (strategic positioning, organizational design, governance systems and identity) over long periods. The longitudinal cross-case analysis reveals different hybrid responses made of various forms of segmentation and blending. Furthermore, it informs the debate on the stability of hybrid responses by tracking various hybrid response paths.